Analisis Butir Soal Ujian Semester Ganjil Kimia Kelas X SMA Negeri 1 Perbaungan - Ria Atika Purba; Nora Susanti; Rosna Rosna (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2019)
The purpose of this study is to find out the quality of the odd chemistry semester exam questions of class X IPA 1 Perbaungan 2017/2018 school year based on qualitative analysis (material, construction, and language), analysis of cognitive level distribution, and quantitative analysis (validity, reliability, power difference, level of difficulty, and effectiveness of deception) using the ANATES V4 program. This study uses a type of quantitative research with descriptive methods. The results of this study are that the content validity in the material is in a very high category, in the construction aspect in the low category and the language aspect in the category is very high. Results based on cognitive domain level distribution are not in accordance with domain level proportions. The results of the study are based on quantitative analysis which is based on validity is 55% valid, and 45% is invalid. Based on reliability is 0.76. Based on the difference in power is good and based on effectiveness the deception is effective.